(untitled) (Journal of the College of Basic Education, 2023)
To identify emotional clarity among kindergarten students. In order to achieve the objectives of the current research, the researcher selected the research community from the students of the Kindergarten Department - College of Basic Education / Al-Mustansiriya University. The emotional clarity scale was prepared from (34) items, and after extracting the psychometric characteristics of validity and reliability, the final version of the scale was produced and applied to the sample. (400) students, and after processing the data statistically, the researcher concluded the following:_ _ Kindergarten students enjoy emotional clarity.